Validez diagnóstica del volumen plaquetario medio en sepsis neonatal: una revisión sistemática: Diagnostic validity of mean platelet volume in neonatal sepsis: a systematic review (Revista Médica de Trujillo, 2022)
A systematic review study was carried out according to the standards of the PRISMA guide. We searched Medline, Pubmed, Central Cochrane and Embase databases. Observational studies (case-control and cohorts) that were published no more than 5 years ago and studied MPV as a diagnostic marker of NS, were included. From 60 articles identified, 12 were selected to be analyzed. We found that the diagnostic cut-off point for MPV ranged between 9.2 and 10.8 fL. In addition, the highest reported diagnostic sensitivity was 100%, and the lowest, 70%; while the specificity ranged from 33% to 94.4% according to each study. Conclusion: The MPV has a high sensitivity for the diagnosis of NS, however, the analyzed studies show a highly variable specificity.
Keywords: neonatal sepsis; MPV; diagnostic utility